Evaluating the Impact of System, Information, and Service Quality on User Outcomes in Malaysian Public Hospitals: A Structural Equation Modeling Approach - Abdullah, Muhd Siv Azhar Merican; Aizuddin, Azimatun Noor; Abdul Manaf, Mohd Rizal (Makara Journal of Health Research, 2025)
Background: Increasing use of hospital information systems (HIS) underscores the need to evaluate their impact on User Satisfaction and Perceived Net Benefits. This study investigated the connections among outsourced System Quality, Information Quality, Service Quality, Perceived Usefulness, User Satisfaction, and Perceived Net Benefits in the context of Malaysian public hospitals. Methods: Data were collected from 1,376 healthcare personnel across six public hospitals and analyzed using structural equation modeling through analysis of moment structures grounded in the DeLone and McLean Information Systems Success Model. Results: System and Service Qualities significantly influenced User Satisfaction and Perceived Usefulness, while Information Quality impacted Satisfaction indirectly. Perceived usefulness emerged as the strongest predictor of Perceived Net Benefits, followed by User Satisfaction, emphasizing their crucial mediating roles. Service Quality substantially impacted user perceptions, highlighting the relevance of technical support and system reliability. Conversely, Information Quality had a less direct effect, reflecting its dependence on user satisfaction for driving benefits. Conclusions: These results underscore the relevance of improving System and Service Qualities to enhance HIS effectiveness. The practical implications include prioritizing system upgrades, responsive support, and user training to maximize satisfaction and perceived benefits.